Volatile hydrocarbons inhibit methanogenic crude oil degradation - Sherry, Angela; Grant, Russell J.; Aitken, Carolyn M.; Jones, Martin; Head, Ian M.; Gray, Neil D. (Frontiers in Microbiology, 2014)
Methanogenic degradation of crude oil in subsurface sediments occurs slowly, but without the need for exogenous electron acceptors, is sustained for long periods and has enormous economic and environmental consequences. Here we show that volatile hydrocarbons are inhibitory to methanogenic oil biodegradation by comparing degradation of an artificially weathered crude oil with volatile hydrocarbons removed, with the same oil that was not weathered. Volatile hydrocarbons (nC5-nC10, methylcyclohexane, benzene, toluene and xylenes) were quantified in the headspace of microcosms. Aliphatic (n-alkanes nC12-nC34) and aromatic hydrocarbons (4-methylbiphenyl, 3-methylbiphenyl, 2-methylnaphthalene, 1-methylnaphthalene) were quantified in the total hydrocarbon fraction extracted from the microcosms. 16S rRNA genes from key microorganisms known to play an important role in methanogenic alkane degradation (Smithella and Methanomicrobiales) were quantified by quantitative PCR. Methane production from degradation of weathered oil in microcosms was rapid (1.1 ± 0.1 µmol CH4/g sediment/day) with stoichiometric yields consistent with degradation of heavier n-alkanes (nC12-nC34). For non-weathered oil, degradation rates in microcosms were significantly lower (0.4 ± 0.3 µmol CH4/g sediment/day). This indicated that volatile hydrocarbons present in the non-weathered oil inhibit, but do not completely halt, methanogenic alkane biodegradation. These findings are significant with respect to rates of biodegradation of crude oils with abundant volatile hydrocarbons in anoxic, sulphate-depleted subsurface environments, such as contaminated marine sediments which have been entrained below the sulfate-reduction zone, as well as crude oil biodegradation in petroleum reservoirs and contaminated aquifers.